Curriculum Integration in Leadership and Entrepreneurship Development for Mosque Manager Education - Dani, Akhmad Anwar; Mudofir, Mudofir; Munadi, Muhammad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This article focuses on implementing curriculum integration in developing leadership and entrepreneurship in mosque manager education at STIDKI Ar-Rahmah. The type of research used is qualitative with a case study approach. The data were collected using a qualitative approach using interviews with the Chairperson, Vice Chairperson, Head of Study Programmes, secretary of study programs, lecturers, students, and alumni of STIDKI Ar-Rahmah as well as observations of various related activities. Data analysis used Milles Hubberman interactive data analysis model: data reduction, data presentation, and drawing conclusions. The results of the analysis show that the development of leadership and entrepreneurship is carried out by instilling basic values through several related courses, developed with several student programs managed by BEM, involving students in the management of the foundation's business units, and providing direct experience of the mosque management process in courses held at the stakeholder mosque.